2017
DOI: 10.1007/s10924-017-1144-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lignocellulose Fillers on Properties Natural Rubber Composites

Abstract: The present article presents unreported yet in the subject literature examinations of the effect of a lignocellulose filler obtained from an alkalized wheat straw treated with di-potassium phosphate on the properties of natural rubber composites. The thermal and mechanical properties as well as the fire hazard of the composites obtained were tested also in the presence of an additive flame-retardant compound (poly(ammonium phosphate)), exploiting the synergism of its action with pentaerythritol, antimony triox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Modulus of elasticity values of the composites was generally shown to increase as filler loadings increased in all cases attributable to chemical bonding occurring between the biofillers and the polymer. [23][24][25] Polyhydroxybutyrate biopolymer composites with cellulosic fillers have not been fully characterized and literature reports on PHB composites are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Modulus of elasticity values of the composites was generally shown to increase as filler loadings increased in all cases attributable to chemical bonding occurring between the biofillers and the polymer. [23][24][25] Polyhydroxybutyrate biopolymer composites with cellulosic fillers have not been fully characterized and literature reports on PHB composites are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the enormous quantity of straw, its utilization to the utmost extent is now demanding attention in the major cereal-growing areas of the world. Up to date, only a few research papers have been published to improve and verify the physical, mechanical, barrier and damping properties of bioelastomer composites with the addition of straw [35][36][37]. Generally, researchers focus their interests mainly on thermoplastic polymers containing cereal or plant straw as a filler.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the straw vulcanizates exhibited significant increase in tear strength and hardness, high values of damping coefficients, and satisfactory strength properties. The effect of alkalized wheat straw treated with dipotassium phosphate on the thermal, mechanical and fire hazard properties of natural rubber was reported by Rybinski, Syrek, Maslowski, Mied-zianowska, Strezelec, Zukowski and Brade [12]. It was found that the bio-fillers in the presence of added fire retardant increased the resistance of the composites to fire without significant adverse effect on the mechanical properties of the rubber composites.…”
Section: Introductionmentioning
confidence: 80%